Comparison of bone cell viability and proliferation in 3D scaffold to Monolayer cell culture - Azizi, Faezeh; Omidpanah, Sahar; Moradi, Afshin; Hossini, Mohammad Ali; Aliakbari, Fereshte; Shariatpanahi, Samira (Archives of Men's Health, 2018)
Introduction: Today, due to high rates of accidents and fractures leading to bone defects and due to the limited possibility of bone graft bonding, using the patient’s cell culture on appropriate scaffolds and transferring it to the defect area is suggested as one of the treatment plans. Materials and methods: Bone samples of 8 male subjects that were under craniotomy surgery in the hospital were collected. First, the samples were cut into smaller pieces and then, transferred to incubator culture dishes. Two weeks later, the osteoblast activity on the bone matrix began and on average, the cells covered the dishes within two weeks. The first generation of the cells was removed by Trypsin_EDTA method from the opaltes, then were divided into two parts, one was added to alginate gel and the other to monolayer culture. In order to prove the osteoblast activity on the bone matrix and investigate these activities, Van Kossa staining method was used, and also to investigate the cell viability, MTT method was employed. Results: There was a significant difference in the number of the cells created in alginate gel and those created in monolayer after two weeks (P <0.001). Moreover, the difference between mean cell counts in alginate gel and monolayer was statistically significant (P < 0.001). The results of the MTT test in second week showed that the number of alive cells is significantly higher in alginate gel (P <0.001). Finally, the result of the Van Kossa method proved extracellular matrix in both experimental groups. Conclusion: Results showed that alginate gel better can support duplication and survival of osteoblasts compared to monolayer culture. This may be attributed to the biological properties of this gel; alginate gel porosity provides conditions under which cellular and metabolic activities are accelerated.